ANALISIS PENGARUH HARGA, KEUNGGULAN PRODUK, DAN PROMOSI TERHADAP KEPUTUSAN MENGGUNAKAN JASA FUMIGASI (STUDI KASUS PT. SUCOFINDO CABANG SEMARANG) - Angraini - Puspitasari; Rif’ah Dwi Astuti; Kurniani - Kurniani (JOBS (Jurnal Of Business Studies), 2017)
The increasing need for fumigation services causes many companies to compete in these services, thus affecting the frequency of service use in PT. Sucofindo Semarang Branch. This research aims to analyze the influence of price, product excellent and promotions toward decision to use fumigation service case study on PT. Sucofindo Semarang Branch. The technique of analysis used in this research was multiple linear regression analysis. The population is the customer who has ever used wood fumigation service at PT. Sucofindo Semarang Branch. The accidental sampling has been applied as the sample technique and the sample are 53 respondents who are wood industry using fumigation service. The results of t-test showed that price partially got negative significant influence toward decision to use fumigation service at PT. Sucofindo Semarang Branch. Product excellent and promotions partially got positive significant influence toward decision to use fumigation service at PT. Sucofindo Semarang Branch. Based on the result of F-test, the price, product excellent and promotions simultaneously got significant influence toward decision to use fumigation service at PT. Sucofindo Semarang Branch. This means that if the price, product excellent and promotions done correctly and continuously, decision to use fumigation service increasing. Based on the adjusted R2, 61.9% influence in the fumigation service decision at PT. Sucofindo Semarang Branch could be explained by price, product excellent and promotion, while the rest of 38.1% was explained by the other variables outside the model. In the implementation of PT. Sucofindo Semarang Branch should pay more attention to product excellent because it has the greatest effect. This can be done through continuous improvement of service quality.